Creating 12‐lead electrocardiogram waveforms using a three‐lead bedside monitor to ensure appropriate monitoring. Issue 6 (5th October 2020) - Yoneyama, Kihei; Naka, Mayumi; Harada, Tomoo; Akashi, Yoshihiro
Abstract : How do you place the three electrodes to create waveforms for leads I, II, III, aVR, aVL, aVF, and V1‐V6?